Comparative efficacy of Diazepam, Ketamine, and Diazepam-Ketamine combination for sedation or anesthesia in cockerel chickens - Mahmud, Muhammad Abdullahi; Shaba, Peter; Yisa, Helen Yarubi; Gana, James; Ndagimba, Ruth; Ndagi, Silas (Journal of Advanced Veterinary and Animal Research, 2014)
The comparative efficacy of Diazepam, Ketamine, and Ketamine-Diazepam combination was assessed in adult chickens. The chickens (n=30) were divided into three equal groups (G-1, G-2 and G-3), and were administered with Diazepam dosed at 0.5 mg/kg body weight (b.wt.), Ketamine HCL dosed at 20 mg/kg b.wt., and Ketamine HCL (dosed at 10 mg/kg b.wt.) combined with Diazepam (dosed at 2 mg/kg b.wt.) through intramuscular (IM) route. The means of induction period, duration of sedation or anesthesia, full recovery period and duration of analgesia were significantly (p?0.05) differed among the groups. Also, the clinical and hematological parameters measured before and after the sedation or anesthesia within the groups were found to be differed significantly (p?0.05) from each other. It was concluded that Diazepam dosed at 0.5 mg/kg b.wt. (IM) can be used in cockerels. However, combination of Ketamine (at 10 mg/kg IM)-Diazepam (at 2 mg/kg b.wt. IM) is preferably recommended as this combination is comparatively safer, and minimizes the pains elicited from the surgical procedure of using Diazepam alone. DOI: http://dx.doi.org/10.5455/javar.2014.a24 J. Adv. Vet. Anim. Res., 1(3): 107-113, September 2014